Pediatricians’ Perceptions Toward Do Not Resuscitate: A Survey in Saudi Arabia and Literature Review - Aljethaily A (Advances in Medical Education and Practice, 2020)
Abdulrahman Aljethaily,1 Turki Al-Mutairi,1 Khalid Al-Harbi,1 Saleh Al-Khonezan,1 Abdallah Aljethaily,2 Hossam S Al-Homaidhi2 1College of Medicine, Al-Imam University, Riyadh, Saudi Arabia; 2Al-Yamamah Hospital (Ministry of Health), Riyadh, Saudi ArabiaCorrespondence: Hossam S Al-HomaidhiDepartment of Pediatrics, Al-Yamamah Hospital, PO Box 103168, Riyadh 11695, Saudi ArabiaTel +966 11 491 4444Email hossam50@gmail.comObjective: To explore the pediatricians’ attitudes and perceptions toward do-not-resuscitate (DNR) orders in a specific region of the world not fully explored before.Methods: A cross-sectional study was conducted between March 4 and May 30, 2018. Pediatricians from three public hospitals in the city of Riyadh were asked to respond to a questionnaire consisting of 22 questions designed to meet the objectives of our study.Results: A total of 203 pediatricians (51.2% female) completed the questionnaire, both junior pediatricians (JPs) and senior pediatricians (SPs). A majority (58.9% of JPs and 61.4% of SPs) thought patients have the right to demand intensive care, despite their terminal illness. Half the participants in both groups thought that DNR is a physician’s decision. Only 9.3% of JPs and 12.5% of SPs felt comfortable discussing DNR with patients/families. Medical school was also a source of knowledge on DNR issues, mainly for JPs (40.2% of JPs vs 20.8% of SPs, P=0.005). Half the participants felt that DNR is consistent with Islamic beliefs, while 57.9% of JPs vs 41.7% of SPs felt they are legally protected. Hospital policy was clear to 48.6% of JPs vs 66.7% of SPs, while procedure was clear to 35.5% of JPs vs 49% of SPs.Conclusion: Several factors are present that may hinder DNR implementation, such as doubts concerning being legally protected, doubts concerning consistency with Islamic sharia, unclear policies and procedures, and lack of training and orientation on DNR issues. Policies may need to include patients as decision-makers.Keywords: DNR policies, DNR implementation, “shared decision-making” paradigm, attitude toward DNR